FUNGSI DAN MAKNA AFIKS BAHASA BUNGKU - Muh. Asri B. (Multilingual, 2013)
The function and meaning of affix in the Bungku language is described in this paper. The paper is categorized as descriptive research, which is described the facts or phenomenon of language in natural way. The method which is applied is the descriptive one, combined with the interviews and documentations techniques In the result, it is showed that affixes on Bungku language have beenclassified into prefix, suffix, infix and confix in certain words construction which has certain meaning and function. Generally, the function of affix in bungku language is to form the noun and verbs. Later, this affix has variative meaning. It has meaning as subject which has to do something, to do an action with tools, the most of, and to make something into something’s else.